Biliteracy development in a rural primary school of Limpopo Province : an ethnographic case study - Lebese, Molatelo Prudence (University of Limpopo (Turfloop Campus), 2012)
The research reported in this mini-dissertation is an ethnographic case study which sought to investigate the development of biliteracy in one of the rural primary schools in the Limpopo province. Its focus is on how Grade 3 learners engage with texts and the strategies that teachers use to promote biliteracy (in English and Sepedi). Data collection methods included classroom observation, semi-structured teacher interviews and analysis of teaching and learning materials and the print environment. A brief analysis of the school’s language policy was also completed. The research revealed that the learners are hardly being taught to read and write whether in Sepedi, (their home language) or in English. While the school language policy states that English should be introduced in Grade 2, it is actually taught only in Grade 3. Additionally, as the learners do not understand English, the teachers frequently code-switch into Sepedi and therefore the learners hardly get any exposure to English. Many other negative aspects were uncovered. Out of the 28 lessons scheduled to be observed only 20 lessons actually took place. The learners are therefore not actually spending the allocated time on literacy development. The teaching is highly routinised with teachers, by and large, using an approach that emphasises repetition and rote-learning. The learners hardly ever get a chance to engage with texts independently. Even the textbooks available are not used but are stored away in the cupboards. Teachers painstakingly copy material from the textbooks on to the chalkboard and learners then copy this into their exercise books. The classroom environment is uninspiring, as there are hardly any learning materials on display. The interviews showed that the teachers had not been adequately trained to teach literacy and were in fact unaware of more effective ways of getting learners to engage with texts. They saw themselves as victims of frequent policy and curricular changes and blamed Government for poor training and lack of resources. The study in fact confirms findings of earlier research that the acquisition of literacy is simply not taking place in the poor, rural schools of South Africa and there is indeed a crisis in education in these schools.
Thesis (M.A. (Translation Studies and Linguistics)) --University of Limpopo, 2012
Keywords: Ethnography; Language development; Biliteracy; 372.65; Education, Bilingual -- South Africa -- Limpopo Province; Education, Primary